2016
DOI: 10.1021/acs.orglett.6b03267
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Polycyclic γ-Lactams and Related Heterocycles via Electron Catalysis

Abstract: Cascade radical cyclization of 1,6-enynes for the construction of biologically important polycyclic γ-lactams and related heterocycles is reported. In these radical cascade processes, three new C–C bonds are formed and transition metals are not required to run these sequences. The mild reaction conditions, broad substrate scope, and the importance of the heterocyclic products render the approach valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…To realize the one‐pot synthesis of bicyclic pyrrolidine derivatives 1 , the preparation of the key intermediate, 1,6‐enyne 4 a became our initial focus. Intermediate 4 a was readily obtained through the allylic substitution of propargyl amine 2 a with Morita‐Baylis‐Hillman adduct 3 a mediated by a Lewis base (LB) catalyst (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…To realize the one‐pot synthesis of bicyclic pyrrolidine derivatives 1 , the preparation of the key intermediate, 1,6‐enyne 4 a became our initial focus. Intermediate 4 a was readily obtained through the allylic substitution of propargyl amine 2 a with Morita‐Baylis‐Hillman adduct 3 a mediated by a Lewis base (LB) catalyst (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Studer and co‐workers developed a versatile method for the synthesis of 2‐pyrrolidinone derivatives via a cascade radical cyclization of 1,6‐enynes and anilines using lithium iodide (LiI) as the initiator (Scheme 1). [15] This reaction formed three new C−C bonds in one‐step without the need for transition metals. While determining the optimal conditions for the synthetic transformation, they found that the absence of initiators or the addition of transition metal salts, such as CuI and FeI 2 , resulted in unsatisfactory yields.…”
Section: Radical Cyclization Of 1n‐enynesmentioning
confidence: 99%
“…It consists of the following key steps: (i) initial formation of diazonium salt A via reaction of aniline 50 with isoamyl nitrite; (ii) interaction of A with LiI to afford the aryl radical B; (iii) chemoselective radical addition of B to the activated alkene of N-allyl propiolamides 49 to give tertiary alkyl radical C; (iv) 5-exo cyclization of radical C leading to vinyl radical D; (v) intramolecular cyclization of radical D onto the arene produces the cyclohexadienyl radical E; (vi) deprotonation of E with alcoholate derived from isoamyl nitrite to afford arene radical anion F; and (vii) oxidation by liberating an electron gives polycyclic g-lactam product 51. 48…”
Section: Radical Mediated Cyclizationsmentioning
confidence: 99%